2018
DOI: 10.1093/jjco/hyx193
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance hormonal therapy after treatment with medroxyprogesterone acetate for patients with atypical polypoid adenomyoma

Abstract: Background: As atypical polypoid adenomyoma (APA) has been reported to be a hormone-related tumor, we aimed to analyze the efficacy and safety of maintenance hormonal therapy after fertility-preserving treatment of these patients with medroxyprogesterone acetate (MPA). Methods: Data were retrospectively analyzed from patients with APA who were treated with a fertility-preserving regimen including MPA between October 2001 and December 2011. Eighteen patients were treated with MPA and 14 (77.8%) achieved either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Thirteen studies were assessed for eligibility; after applying exclusion criteria, two of them were excluded. The last 11 retrospective studies with a total of 237 APA were included in the quantitative systematic review . Two of the included studies reported overlapping data and were considered as one study in the data analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies were assessed for eligibility; after applying exclusion criteria, two of them were excluded. The last 11 retrospective studies with a total of 237 APA were included in the quantitative systematic review . Two of the included studies reported overlapping data and were considered as one study in the data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…For the “unbiased assessment of the study endpoint” domain, five studies were categorized as low risk of bias since they performed histological examination at every follow‐up visit . Six studies were classified as unclear risk because they performed histological examination only when ultrasonographic findings were suspicious, or if they did not specify whether histological examination was performed at every follow‐up visit …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations